The Influence of Altruistic Preferences on the Race to the Bottom of Welfare States - Ulrich Hendel (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
Common tax competition models suggest that welfare states will undercut each other's tax rate to attract taxpayers and keep welfare recipients at bay. This will lead to a zero-taxation outcome in the absence of migration costs or other barriers to migration. This paper develops a two-country framework with mobile altruistic taxpayers and immobile welfare recipients. It shows that under the assumption of taxpayers motivated by warm glow altruism, tax competition leads to unique pure strategy Nash equilibria in taxation which are different from zero given sufficiently strong altruistic preferences. If countries are asymmetric with respect to the number of welfare recipients, pure altruism and inequity aversion preferences support additional unique pure strategy Nash equilibria in which the country with the fewer poor attracts more taxpayers and sets higher taxes. This implies that rich countries may benefit from tax competition.
urn:nbn:de:bvb:19-epub-13999-1
Keywords: H73; D64; H20; 330; tax competition; welfare state; altruism; Steuerwettbewerb; Sozialstaat; Altruismus; Nash-Gleichgewicht; Theorie